Effect of Obstacle Angles on Signal Strength for Different Mounting Elevations of XBee Pro Module in Viral Advertisement System - Mohd Rusdy , Yaacob; Lim , Wee Teck; Nik Anwar, Nik Syahrim (2013)
This paper presents a study on the effect of obstacle angles on signal strength for different mounting elevations of XBee Pro module. The study has been conducted by using two units of XBee Pro modules which each represents a receiver and a transmitter. The transmitter is mounted in three different elevations which are 0.5, 1.5 and 2.5 meter from the ground while the receiver is fixed at the same elevation but at different positions which yield to different angles. When the transmitter continuously transmits the wireless signal carrying its particular address, the receiver will detect the signal address once the range of communication of both receiver and transmitter intersects. The results obtained are the values of signal strength, in percentage, with respect to the obstacle angles between receiver and transmitter for different mounting elevations of transmitter. These data are then converted into graph that illustrates the signal strength characteristics for each mounting elevation. Finally, the best mounting elevation is to be identified based on the result obtained.